أثر القيود المالية على سياسة توزيع الأرباح والآداء المالي للشركات المدرجة في بورصة قطر - ديدوش ،مصطفى; غزيل، محمد مولود (جامعة الوادي University of Eloued, 2024)
The study aimed to focus on analyzing the impact of financial constraints on dividend policy and financial performance of companies listed on the Qatar Stock Exchange between 2019 and 2023. The fixed effects model and the random effects model were adopted to understand the impact of financial constraints on dividend policy and company profitability, considering the COVID-19 crisis that swept through the study period. A sample of 39 companies listed on the Qatar Stock Exchange from various sectors was selected. The study concluded that financial constraints have a negative impact on both dividend policy and financial performance. Additionally, the COVID-19 crisis affected the profitability of companies and their dividend distribution policies.
The Impact of Financial Constraints on Dividend Distribution Policy and Financial Performance of Companies Listed on the Qatar Stock Exchange during the Period (2019-2023)
Keywords: قيود مالية; سياسة توزيع الأرباح; أداء مالي; قطر; كوفيد-19; Financial constraints; dividend policy; financial performance; Qatar; COVID-19